Job Polarization and Jobless Recoveries - Jaimovich, Nir; Siu, Henry E. (The Review of Economics and Statistics, 2020)
Job polarization refers to the shrinking share of employment in middle-skill, routine occupations experienced over the past 35 years. Jobless recoveries refers to the slow rebound in aggregate employment following recent recessions despite recoveries in aggregate output. We show how these two phenomena are related. First, essentially all employment loss in routine occupations occurs in economic downturns. Second, jobless recoveries in the aggregate can be accounted for by jobless recoveries in the routine occupations that are disappearing.